Bacterial Cellulose Membrane Experimentally Implanted in the Peritoneum of Wistar Rats—Inflammatory Immunoreactivity and Oxidative Stress - Santos, Karina Oliveira [UNESP]; Bertolo, Rebecca [UNESP]; de Almeida Ibanez, Natasha Lien; Alves, Mônica Rodrigues; Onuma, Tatiana Pessoa [UNESP]; Ribeiro, Gabriella Costa [UNESP]; de Souza Porto, Anna Julia [UNESP]; Barbeito, Cláudio Gustavo; Pinato, Luciana [UNESP]; Jozala, Angela Faustino; Grotto, Denise; Hataka, Alessandre [UNESP] (MDPI, 2024)
Bacterial cellulose (BC) has been used for various applications; however, studies investigating the immunohistochemical characteristics of the inflammatory and scarring component in BC implanted in the peritoneum in vivo have not yet been fully described. This study aimed to evaluate the systemic and organic safety of BC through oxidative stress, blood, and serum biochemical markers, as well as the late inflammatory response in rats, using histopathology and immunohistochemistry. Forty-three rats (26 males; 17 females) received BC in the peritoneal cavity (implanted group—IG), while twenty-seven rats (12 males; 15 females) served as the control (sham group—SG). Sixty days after surgery, oxidative stress in tissues, blood biochemical markers, and histopathological and immunohistochemical analyses for lymphocytes, macrophages, collagen, and vascular response around the BC were assessed. Only one oxidative stress marker, glutathione peroxidase, was elevated in the liver of IG rats. Creatine kinase MB and lactate dehydrogenase levels were significantly lower in IG animals. Histopathological analysis showed granulomatous inflammation in 93% of IG rats, with 74% of mild intensity. Immunohistochemistry revealed a significant macrophage presence (F4/80), with CD3, CD20, and F4/80 markers indicating differences favoring macrophages. In conclusion, BC implantation in the peritoneum induces a foreign body granulomatous response with prominent macrophage presence (F4/80). Type I and III collagen were observed around the membrane, and vascularization was intense 60 days post-implantation. From a biochemical and oxidative stress perspective, BC seems to be a safe material to be used in the peritoneal cavity.
Keywords: bacterial cellulose; immunohistochemistry; oxidative stress; peritoneal; rat